CUADERNOS DE EJERCICIOS PARA LA ENSEÑANZA DE LA HISTORIA. APUNTES DE UNA EXPERIENCIA - Yusdelis Reyna Acosta (University of Las Tunas, 2018)
El artículo hace referencia a uno de los temas más recurrentes en la enseñanza de la Historia: el desarrollo del pensamiento histórico y crítico en los estudiantes, para ello se necesita la implementación de proyecciones pedagógicas que sean capaces de situarlos como protagonistas del proceso de enseñanza-aprendizaje, que tengan en cuenta la utilización de variadas fuentes que les permitan la elaboración de sus propias conclusiones que conlleven a la confrontación, la discusión y la toma de partido a favor o en contra de determinada actitud o decisión. Como ejemplo de ello se ofrecen actividades que forman parte de uno de los resultados del Proyecto de Investigación Clío Didáctica: la enseñanza de la Historia en la escuela, las mismas constituyen soporte esencial para la docencia. Su utilización ha permitido el incremento del nivel de aprendizaje en los estudiantes, así como su grado de independencia y creatividad. ABSTRACT The article refers to some of the most recurrent topic in the teaching of History: the development of historical and critical thinking in students, which is needed for the implementation of viable educational displays that are able to place students as protagonist of the teaching-learning process, taking into account the use of different sources that enable the development of their own conclusions, views, that lead to confrontation, discussion and match making for or against particular attitude or decision, to be able to put the student in "other place" and why not teach him to reconstruct the story from the practice of research. An example of this activity as part of some of the results of the Research Project "Clio" Teaching offered learning. Its use has allowed increasing the level of learning of the students and their degree of independence and creativity. The systematization of such activities substantiate their value and usefulness for the teaching of History in the Secondary School, is one of the tasks of the project "The historical education of children and young people". KEY WORDS: critical thinking, historical sources, historical knowledge, education, History.